STUDI EFEKTIVITAS KEPEMIMPINAN KEPALA SEKOLAH : Analisis Pengaruh Karakteristik Pribadi, Perilaku Memimpin, Kualifikasi Pekerjaan dan Konteks Tugas Kepala Sekolah Terhadap Efektivitas Kepemimpinan Kepala Sekolah dan Dampaknya Terhadap Peningkatan Kinerja SMP Swasta di Kota Cimahi Jawa Barat - Muljono, Hery (2015)
Penelitianiniberangkatdaripermasalahankinerjasekolah yang belum optimal disebabkanolehsalahsatufaktorbelumefektifnyakepemimpinankepalasekolah.Kajianempiristerhadapkinerja SMP swasta di kotaCimahimenunjukkanhasil yang belummemuaskanterlihatdariprestasiakademiksiswasepertinilaiujiannasional SMP swasta di kotaCimahisebagianbesarberadapadaurutanduapuluhkebawahdibandingkancapaiansiswadari SMP negeri di Kota Cimahi. Mengacupadakelemahantersebut, penelititertarikuntukmelakukanstuditentangefektivitaskepemimpinankepalasekolah yang difokuskankepadaderajatmempengaruhipengikutnyauntukmeningkatkankinerjasekolah. Tujuanutamapenelitianiniadalahmendeskripsikangambaranempirisdanmenganalisismengenaiseberapabesarpengaruhefektivitaskepemimpinankepalasekolahdandampaknyaterhadappeningkatankinerjasekolahdarivariabel-variabelkarakteristikpribadi, perilakumemimpin, kualifikasipekerjaandankontekstugaskepalasekolah. Unit analisiskepemimpinankepalasekolahdanrespondenpenelitianiniadalahpara guru sekolah SMP swasta di kotaCimahi, Jawa Barat. Penelitian ini menggunakanpendekatankuantitatifdengan menerapkan analisisjalur(path analysis) untukmenjelaskandanmenjabarkankondisimasing-masingvariabelsecararinci sertamengkaji hubungankasualitasantarvariabel-variabelpenelitian. Sampel penelitian yang ditelitiadalahseluruhsekolah SMP Swasta di kotaCimahi yang berjumlahsebanyak 24sekolahdenganrespondenpenelitiansebanyak 390 orang (guru) dariseluruh SMP swastatersebut. Temuanpenelitianiniadalah (1) terdapatpengaruhpositifkarakteristikpribadikepalasekolahterhadapefektivitaskepemimpinankepalasekolah, (2) terdapatpengaruhpositifperilakumemimpinkepalasekolahterhadapefektivitaskepemimpinankepalasekolah, (3) tidakterdapatpengaruhpositifkualifikasipekerjaankepalasekolahterhadapefektifitaskepemimpinankepalasekolah, (4) terdapatpengaruhpositifkontekstugaskepalasekolahterhadapefektivitaskepemimpinankepalasekolah, (5)terdapatpengaruhpositifkarakteristikpribadikepalasekolahterhadapkinerjasekolah, (6) tidakterdapatpengaruhpositifperilakumemimpinkepalasekolahterhadapkinerjasekolah, (7) terdapatpengaruhpositifkualifikasipekerjaankepalasekolahterhadapkinerjasekolah (8) terdapatpengaruhpositifkontekstugaskepalasekolahterhadapkinerjasekolah, (9) terdapatpengaruhpositifefektivitaskepemimpinankepalasekolahterhadapkinerjasekolah, (10) terdapatpengaruhpositifkarakteristikpribadi, perilakumemimpin, kualifikasipekerjaan, kontekstugasterhadapefektivitaskepemimpinansecaralangsungdantidaklangsung, dan (11) terdapatpengaruhpositifkarakteristikpribadi, perilakumemimpin, kualifikasipekerjaan, kontekstugasterhadapkinerjasekolahsecaralangsungdantidaklangsungRekomendasipenelitiditujukankepadaDinasPendidikan, YayasanPendidikandanKepalaSekolahadalah (1) kualifikasipekerjaankepalasekolahperludirincidenganlebihjelasdandijadikanrujukandalam proses seleksi, pembinaandanpeniaiankepalasekolah, (2)perludikembangkan program pelatihandanpengembangankepalasekolah yang difokuskanuntukmembangunkarakteristikpribadi, perilakumemimpindankontekstugaskepalasekolah yang dapatmeningkatkanefektivitaskepemimpinankepalasekolahdanpadaakhirnyaberdampakterhadappeningkatankinerjasekolahsecarakeseluruhan. Kata Kunci: Efektivitaskepemimpinan,kepalasekolah, karakteristikpribadi, perilakumemimpin, kualifikasipekerjaan, kontekstugas, kinerjasekolah This study starts from the problems of school performance that is not optimal due to one factor of in effective school leadership.The performance of Junior High School in Cimahi, West Java has shown unsatisfactory result today, which can be seen from the academic achievement of Private Junior High School's students, such as the result of the national examination which mostly under 20th rank compared to the achievement of Public Junior High School's students in Cimahi. Based on that weakness, the researcher interested inconducting a study about the effectiveness of principal leadership which is focused on the degree to influence subordinate for improving the school performance. The main aim of the present study is to describe empirical description and to analyze how far the influence of principal leadeship's effectiveness and its impact to the increasing of the school performance from variables. The variabels are personal characteristic, leading behavior, work qualification, and the task context of the principal. The subject and respondents of the present study are teachers from Private Junior High School in Cimahi, West Java. This study uses qualitative approach by applying path analysis to desribe and explain each variable condition in detail and to examine the causality relationship between the variables. The research sample studied is the entire private junior high school in the town of Cimahi, calculated to as much as 24 schools with research respondents as many as 390 people (teachers) from all the private junior high school. The result of the present research are (1) there is a positive influence from principal's personal characteristic to the effectiveness of the principal leadership, (2) there is a positive influence from principal's leading behavior to the effectiveness of the principal leadership, (3) there is no positive influence from principal's work qualification to the effectiveness of the principal leadership, (4) there is a positive influence from principal's task context to the effectiveness of the principal leadership, (5) there is a positive influence from principal's personal characteristic to the school performance, (6) there is no positive influence from principal's leading behavior to the school performance, (7) there is positive influence from principal's work qualification to the school performance, (8) there is a positive influence from principal's task context to the school performance, (9) there is a positive influence from principal leadership effectiveness to the school performance, (10) there is a positive influence from personal characteristic, leading behavior, work qualification, and task context to the leadership effectiveness directly or indirectly, (11) there is a positive influence from personal characteristic, leading behavior, work qualification, and task context to the school performance whether directly or indirectly. The recommendation from the result are (1) work qualification of principal is needed to be stated in detail and clear. It can be a reference for stakeholders in selection, training, and evaluating process of the principal. (2) Training and developing program which are focused on developing principal's personal characteristic, leading behavior, and task context are needed to be developed. It can increase the effectiveness of principal leadership and give effect to the improvement of the whole school performance. Key words: Leadership effectiveness, principal, personal characteristic, leading behavior, work qualification, task context, school performance.